Rainfall variability in Southern Africa, its influences on streamflow variations and its relationships with climatic variations - Valimba, Patrick (Rhodes University, Faculty of Science, Institute for Water Research, 2005)
Hydrological variability involving rainfall and streamflows in southern Africa have been often studied separately or have used cumulative rainfall and streamflow indices. The main objective of this study was to investigate spatio-temporal variations of rainfall, their influences on streamflows and their relationships with climatic variations with emphasis on indices that characterise the hydrological extremes, floods and droughts. It was found that 60-70% of the time when it rains, daily rainfalls are below their long-term averages and daily amounts below 10 mm are the most frequent in southern Africa. Spatially, climatologies of rainfall sub-divided the southern African subcontinent into the dry western/southwestern part and the "humid" eastern and northern part. The daily amounts below 20 mm contribute significantly to annual rainfall amounts in the dry part while all types of daily rainfall exceeding 1 mm have comparable contributions in the humid part. The climatologies indicated the highest likelihood of experiencing intense daily events during the core of the wet seasons with the highest frequencies in central Mozambique and the southern highlands of Tanzania. Interannual variations of rainfall indicated that significant changes had occurred between the late-1940s and early-1980s, particularly in the 1970s. The changes in rainfall were more evident in the number of daily rainfall events than in rainfall amounts, led generally to increasing early summer and decreased late summer rainfall. It was also found that intra-seasonal dry day sequences were an important parameter in the definition of a rainy season's onset and end in southern Africa apart from rainfall amounts. Interannual variations of the rainy season characteristics (onset, end, duration) followed the variations of rainfall amounts and number of events. The duration of the rainy season was affected by the onset (Tanzania), onset or end (tropical southern Africa - southwestern highlands of Tanzania, Zambia, northern Zimbabwe and central Mozambique) and end (the remaing part of southern Africa). Flow duration curves (FDCs) identified three types of rivers (ephemeral, seasonal and perennial) in southern Africa with ephemeral rivers found mainly in the dry western part of the region. Seasonal streamflow patterns followed those of rainfall while interannual streamflow variations indicated significant changes of mean flows with little evidences of high and low flow regime changes except in Namibia and some parts of northern Zimbabwe. It was, however, not possible to provide strong links between the identified changes in streamflows and those in rainfall. Regarding the influences of climate variability on hydrological variability in southern Africa, rainfall variations in southern Africa were found to be influenced strongly by ENSO and SST in the tropical Indian ocean and moderately by SST in the south Madagascar basin. The influence of ENSO was consistent for all types of daily rainfall and peaks for the light and moderate (< 20 mm) events in the southern part and for the intense events in the northern part. SST in the tropical Indian ocean influence the light and moderate events while SST close to the region influence the heavy events. However, the relationships experienced significant changes in the mid-1950s and in the 1970s. The former changes led to improved associations while the latter deteriorated or reversed the relationships. The influences of climatic variables on streamflows and rainy season characteristics were inferred from the rainfall-streamflow and rainfall-climatic variables relationships.
Keywords: Rain and rainfall -- Africa, Southern; Climatic changes -- Africa, Southern; Streamflow -- Africa, Southern